1978
DOI: 10.1063/1.435956
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of phase transitions in bidimensional monolayers

Abstract: We propose a theoretical study of phase transitions in long hydrocarbon chain monolayers. lying on aqueous substrate. We use a model taken from that applied by DiMarzio to liquid crystals: each molecule can occupy several aligned sites on the holder (I to 5 for us). We also take into account the attractive interactions between the hydrocarbon chains in the framework of a mean field approximation: it gives a first order phase transition in a diagram showing surface pressure variations in terms of the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
0
23
0
1
Order By: Relevance
“…In the density region 0<n<x~ -1 there is a flat co-existence region corresponding to the critical isotherm of a two-dimensional gas-liquid condensation of x3-mers [6][7][8]. If fi%(1)>2x3 ~ ae(X~) the isotherms would display a van der Waals loop in the domain 0 < n < x3 -1.…”
Section: --Flc]e](x3--x~)---fle]rmentioning
confidence: 99%
See 1 more Smart Citation
“…In the density region 0<n<x~ -1 there is a flat co-existence region corresponding to the critical isotherm of a two-dimensional gas-liquid condensation of x3-mers [6][7][8]. If fi%(1)>2x3 ~ ae(X~) the isotherms would display a van der Waals loop in the domain 0 < n < x3 -1.…”
Section: --Flc]e](x3--x~)---fle]rmentioning
confidence: 99%
“…For instance molecular clustering [12] and dimerization [7] of the pentadecanoic acid molecules have been postulated to account for the low pressures observed. A mean field approach has been employed previously to describe a twodimensional gas-liquid condensation of adsorbed monolayers of rigid rod-like molecules [6,7] which bears some similarity to the experimentally observed condensation of dilute pentadecanoic acid monolayers. Here we extend an analysis of adsorption for rigid rod-like molecules which interact with long range dispersion interactions [7] to include anisotropic rod-like molecules which have several interconvertible configurational states which have different molecular contact areas on the surface.…”
Section: Introductionmentioning
confidence: 98%
“…However, for longer chains (consisting of at least four segments) we observe two-phase transitions: the first corresponds to gas-liquid condensation and the other is the orderdisorder transition. Moreover, for the molecules containing 5 segments Frippo et al (33) have found that for carefully chosen temperatures, the transition from a dilute disordered state to a dense ordered (solid) state occurred without any intermediate (liquid) state. The transitions leading to the ordered phase could be either the first-order or continuous transitions, depending on the temperature.…”
Section: Introductionmentioning
confidence: 98%
“…An early contribution to the theoretical study of phase transitions in monolayers of large molecules has been made by Frippo et al (33). Although this model was proposed to describe monolayers of long hydrocarbon chains spread at the gas-liquid interface, its theoretical foundation would remain unchanged if one wanted to apply it to gas-solid systems.…”
Section: Introductionmentioning
confidence: 99%
“…Mafé et al [70] empregaram um modelo de campo médio baseado na aproximação quase-química para as moléculas na superfície e obtiveram boa concordância qualitativa para a fase gasosa das isotermas. Outros modelos da literatura são o de Firpo et al [71] e o de Schmid-Schick [72], sendo que este último conseguiu obter duas transições de fase fluido-fluido.…”
Section: 5-estudo De Monocamadas Através De Modelos De Redeunclassified